Rhetoric, logic, and experiment in the quantum nonlocality debate - Graft Donald A. (Open Physics, 2017)
This paper argues that quantum nonlocality (QNL) has not been rigorously proven, despite the existence of recent Einstein-Podolsky-Rosen-Bohm (EPRB) experiments that are claimed to be ‘loophole-free’. First, readers are alerted to rhetorical arguments, which are unfortunately often appealed to in the QNL debate, to empower readers to identify and reject such arguments. Second, logical problems in QNL proofs are described and exemplified by a discussion of the projection postulate problem. Third, experimental issues are described and exemplified by a discussion of the postselection problem. The paper concludes that QNL has not been proven and that locality cannot be excluded.